The Role of Compensation and Work Culture on Perceived Organizational Support and Its Impact on Organizational Citizenship Behavior of PT. ARP Employees - Febrianti, Erly Yusnita; Riyanto, Setyo (Dinasti Publisher, 2025)
This study examines the influence of compensation and work culture on Perceived Organizational Support (POS) and its impact on Organizational Citizenship Behavior (OCB) among employees of PT ARP. Using a quantitative approach with Structural Equation Modeling (SEM) and SmartPLS software, data were gathered from 92 employees through a questionnaire. The findings reveal that compensation and work culture positively and significantly influence POS. Furthermore, both variables also have a positive and significant direct effect on OCB. POS serves as a mediating variable, amplifying the impact of compensation and work culture on OCB. These results highlight the importance of fair compensation and a supportive work culture in enhancing POS, which fosters extra-role behaviors such as OCB. This study underscores the role of organizational policies in creating a work environment that promotes employee engagement and productivity through improved perceptions of support and citizenship behaviour.